An interaction study of online learning satisfaction with parent-child relationships and trait coping styles - Wen, Leji; Xu, Weizhuo; Yan, Xiaoyue; Lin, Xin; Shao, Chen; Zhang, Lei (Frontiers in Psychiatry, 2024)
This study aims to explore the factors affecting online learning satisfaction (OLS) among students and their interaction with parent-child relationship (PR) and trait coping style (TCS). A web-based questionnaire was employed, encompassing general information, the Trait Coping Style Questionnaire (TCSQ), and queries related to OLS. A total of 1,287 valid questionnaires were collected, with 593 from junior high school students, 197 from high school students, and 497 from university students. Our findings indicate that parent-child relationship (PR), positive coping style (PCS), and learning status (LS) showed a positive correlation with OLS (r=0.110, P<0.001; r=0.786, P<0.001). Conversely, negative coping style (NCS) presented a negative correlation with OLS (r=-0.186, P<0.01). Multiple regression analysis of OLS reveals that PR has a significant impact on OLS (P<0.001, β=0.291), as does LS (P<0.001, β=0.767). However, trait coping styles (TCS) appear to have no significant effect on OLS. Notably, PR plays a significant and positive mediating role between LS and OLS, with a mediation effect of 0.0132 (P<0.05), accounting for 1.682% of the total effect. These findings suggest that strengthening parent-child interactions and fostering adaptive coping mechanisms could play a crucial role in enhancing students' satisfaction with online education. Such improvements could potentially contribute to superior academic outcomes and overall student well-being.The COVID-19 pandemic has disrupted the traditional education mode, leading many young individuals to explore alternatives through online platforms(Pokhrel and